(untitled) (Indian Journal of Animal Production and Management, 2026)
A study was conducted to understand consumer perception towards meat and meat products consumption in Tirupati city. The city of Tirupati has witnessed a sharp rise in households, which is evident from the rapid expansion of the city outskirts by means of real-estate developments. This poses a greater scope for meat startups to be established in the rapidly developing city. A total of 200 respondents were randomly selected and interviewed. Data were collected using a pre-tested structured interview schedule through personal interviews. The study group comprised 76 males and 124 females. The educational background of respondents was found to vary between uneducated and PG & PhD levels. The overall mean age of the consumers was found to be 33.5, of which the majority (45%) belong to the middle age group. The study revealed that most of the consumers ate meat for taste (67%) and health benefits (33%) and usually consume meat twice a week (51%). The most preferred meat was chicken (53%), followed by chevon (21%), seafood (fish, prawns) at 16%, and other meat at 10%. Gravy-type meat products were most preferred, followed by biryani (19%) and fried meat products (15%). Most of the consumers (63%) opined that meat has good cholesterol (HDL) and (28%) as bad cholesterol (LDL), whereas (9%) opined as both. The willingness to purchase chilled/frozen meat was very low (5%). The acceptance of the respondents towards processed meat products such as pickles was 80%, and comminuted meat products were at 20%, respectively. The majority of the respondents (82%) believed that overconsumption of meat leads to heart problems and other diseases. Unfortunately, (78%) of the respondents have no idea about what kind of vitamins and minerals are present in meat. Most of the consumers said that the ideal methods for cooking are boiling (78%) and frying (22%). Only (40%) of the respondents have awareness about zoonotic diseases. Food safety has emerged as an important global issue with international trade and public health implications. The current study also revealed that most of the respondents have no idea about laws pertaining to food safety. The results indicated that most respondents consume meat for taste and as a cultural tradition. However, the majority of the consumers lack a scientific backdrop about fresh meat and processed meat, which can further be overcome by conducting extensive awareness programs and advertisements by government agencies and entrepreneurs in the meat trade. Consumer awareness about the scientific handling of meat can safeguard their health and also pave the way for huge investments in meat startups in developing cities.